Integrasi Nilai-Nilai Moderasi Beragama dalam Pendidikan Inklusif di MTs Negeri 3 Ponorogo - Ajizah, Ratna Utami Nur; Putra, Khalis Zamrani; Anam, Wafda Khoirul (Proceedings of Annual Conference for Muslim Scholars, 2023)
The study examines the incorporation of religious moderation values into inclusive education at MTs Negeri 3 Ponorogo. The research focuses on implementing these values in inclusive educational practices. The research aims to explore the impact of integrating religious moderation values on fostering a tolerant and harmonious school atmosphere. Employing a qualitative approach with interviews, participatory observations, and document analysis, the study reveals the success of MTs Negeri 3 Ponorogo in integrating religious moderation values into inclusive education. This is evident in activities such as socialization sessions, the selection of a Modis (Religious Moderation) Ambassador, mosque tilik activities emphasizing care for places of worship, and classroom learning approaches embedded in the context of religious moderation. The discussion outlines research findings, underscoring the success of integrating religious moderation values in shaping an inclusive educational environment that supports tolerance and harmony. In conclusion, the implementation of religious moderation values in MTs Negeri 3 Ponorogo positively influences the development of a more harmonious and inclusive school community.